Small Family Farms, A Review in Indonesian Context - Purnawan, Endar; Brunori, Gianluca; Prosperi, Paolo (International Journal of Multidisciplinary: Applied Business and Education Research, 2022)
This paper addresses a general description of small family farms in Indonesia. Building on a literature review, it sheds light on the significant role of small family farms in Sustainable Development Goals, family farms in Indonesia and their challenges, as well as on the impact of investments oriented to farmers for food security. The reviews indicate that enabling family farmers to fulfill their roles can affect the acceleration of progress across crucial elements of Sustainable Development Goals. Key challenges faced by the farmers include low technology implementation, limited access to finances, farm size fragmentation, infrastructure and market linkage, the climate factor, and availability and accessibility of fertilizers and seeds. In conclusion, this paper highlights the importance of investment in small family farms for improving access to financial services and public goods, strengthening market linkages, enhancing productivity through research and extension, and investing beyond the farm through a rural non-farm economy and a territorial development perspective.